Pelatihan Penerapan Manajemen Promosi Berbasis Online di Kelurahan Kalisegoro Kecamatan Gunungpati Semarang - Hendra Jaya; M. Miswanto Gunawan (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
The internet is a source of information delivery in the era of revolution 4.0 and is very much needed for villages as a promotional media, marketing media, information media, educational media and communication media which are expressed in the form of websites. Abundant agricultural products have great potential in rural areas. There is a digital gap between rural and urban areas due to the unequal distribution of infrastructure, human resources (HR) and information and communication technology (ICT). This gap influences the lack of ICT utilization at the village level. To realize the principles of openness and accountability which are one of the basic foundations adhered to by the village. In running and administering village government. So it is considered important to have a village website. It is hoped that this website can be used as a means of information media and promotion of the potential that exists in the village as well as for public accountability and transparency. The aim of creating a village website is none other than to publish information on village potential and the existence of the village to the outside world, so that it is easy for many people to know, informing about the Village Profile, Social and Economic Potential, Village Government Organization, Village Statistics, Village News and Gallery as Village Documentation.